2014
DOI: 10.18433/j33c7b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Hepatic Ischemia-Reperfusion Injury on the Function of P-glycoprotein in vivo in Rats

Abstract: -PURPOSE: Ischemia-reperfusion injury is a common complication in liver surgery with oxidative stress related graft failure as a potential complication. The oxidative stress could affect hepatic drug transporters such as P-glycoprotein, which is crucial in the hepatic clearance of certain immunosuppressant drugs. Thus,, it is important to study its function after ischemia-reperfusion injury in vivo. Rhodamine 123 is a fluorescent substrate of P-glycoprotein and its hepatic disposition can be visualized using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Recent studies (Hashimoto and Sanjo, 1997;Ikemura et al, 2009;Parasrampuria et al, 2012;Shaik and Mehvar, 2011;Thorling et al, 2014;Tian et al, 2005aTian et al, , 2005b have shown that IR injury or Hx alters the disposition of drugs. In agreement with these studies, our current investigation showed that IR alone or in combination with Hx (HxIR) would change the systemic pharmacokinetics of FL (...…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Hashimoto and Sanjo, 1997;Ikemura et al, 2009;Parasrampuria et al, 2012;Shaik and Mehvar, 2011;Thorling et al, 2014;Tian et al, 2005aTian et al, , 2005b have shown that IR injury or Hx alters the disposition of drugs. In agreement with these studies, our current investigation showed that IR alone or in combination with Hx (HxIR) would change the systemic pharmacokinetics of FL (...…”
Section: Discussionmentioning
confidence: 99%
“…One of the proposed mechanisms is a modification of mRNA expression induced by proinflammatory cytokines such as IL‐6, IL‐1β, and TNFα . Endotoxin‐induced down‐regulation of drug transporters is another proposed mechanism as well as oxidative stress …”
Section: Comorbidities Associated With Altered Drug Transporter Activitymentioning
confidence: 99%
“…[110][111][112] Endotoxin-induced down-regulation of drug transporters is another proposed mechanism 110,112 as well as oxidative stress. 113,114 Inflammatory bowel diseases are known to induce changes in the intestinal epithelium, such as alteration of permeability, 115 and to be associated with an increase in proinflammatory agents. [116][117][118][119][120] A study conducted in children has analyzed the impact of Crohn disease (CD) on the expression of P-gp.…”
Section: Comorbidities Associated With Altered Drug Transporter Activitymentioning
confidence: 99%